An approach to the recent reception of Hegel's philosophy in Argentina. - Brauer, Daniel (ARFIL y UNL, 2021)
In this interview with Prof. Dr. Daniel Brauer, one of the researchers who has devoted important studies to Hegel's thought and has contributed to its reception in Argentina, some significant moments of his experience as a teacher and researcher in recent decades are highlighted.